Comparative case studies: trip and parking generation at Orenco Station TOD, Portland Region and Station Park TAD, Salt Lake City Region. (April 2019) - Ewing, Reid; Tian, Guang; Park, Keunhyun; Sabouri, Sadegh; Stinger, Preston; Proffitt, David
Abstract: The subjects of this comparative case study are Orenco Station, a transit-oriented development (TOD) in the Portland region, and Station Park, a transit-adjacent development (TAD) in Salt Lake City region. The peak parking demand at Orenco Station is less than one half the Institute of Transportation Engineers (ITE) suburban parking supply guideline. Also, vehicle trip generation rates are about half what is suggested in the ITE guidelines. Vehicle trip generation rates at Station Park show a smaller reduction but still substantial due to the mixed-use nature of Station Park. Parking generation rates are also lower than the ITE guidelines. In terms of metrics often associated with transportation performance, the large-scale TOD dramatically outperforms the large-scale TAD. The adjacent rail station appears to have little effect on the performance of the TAD, but a substantial effect on the performance of the TOD. Highlights: The peak parking demand at Orenco Station TOD is less than one half the ITE suburban parking supply guideline. Also, vehicle trip generation rates at Orenco Station are about half what is suggested in the ITE guidelines. Vehicle trip generation rates at the Station Park TAD are lower than the suburban average due to a mix of land uses. Parking generation rates at Station Park are also lower than the ITE supply guideline. Regarding metrics associated with transportation performance, the large-scale TOD outperforms the large-scale TAD. The adjacent rail station may have a substantial effect on the performance of the TOD but little effect on that of the TAD.